Establishing wMelPop wolbachia Infection among wild aedes aegypti females by optimal control approach (2017)
Wolbachia is a maternally transmitted bacterial symbiont which is known to reduce the vector competence of mosquitoes and other arthropod species. Therefore, Wolbachia-based biocontrol is regarded as a practicable method for prevention and control of dengue and other arboviral infections. In particular, a deliberate infection of Aedes aegypti females with wMelPop Wolbachia strain makes them almost incapable of transmitting dengue and other arboviruses. In this paper, we present and thoroughly analyze a population dynamics model of interaction between wild Aedes aegypti female mosquitoes and those infected with wMelPop Wolbachia strain, which compete for the same vital resources (food, breeding sites, etc.) and share the same locality. Using this model, we demonstrate that the final outcome of the competition essentially depends on the frequency of Wolbachia infection. Further, we apply the optimal control approach and design the control intervention programs based on periodic releases of Wolbachia-carrying females for establishing wMelPop Wolbachia infection in the target locality